Analysis of Limestone Characteristics on the South Coast of Gorontalo Based on Specific Gravity and Water Absorption Tests - Aang Panji Permana; Ronal Hutagalung; Sunarty Suly Eraku; Dewi Rahmawaty Isa (Postgraduate, University of Mataram, 2024)
The southern coast of Gorontalo has complex geological conditions. This is indicated by the strong tectonic influence with the uplift of the Quaternary limestone at high elevations. The distribution of this limestone is very unique because it is located between the dominance of volcanic and plutonic rocks that form the northern arm of Sulawesi. The purpose of this study was to focus on the characteristics of limestone on the south coast of Gorontalo based on specific gravity and water absorption tests. The research methods used to achieve these objectives consist of field geological surveys and laboratory analysis of the specific gravity and water absorption tests of coarse aggregate. The field geological survey consisted of taking limestone samples for laboratory analysis and petrological analysis. The results showed that the limestone on the southern coast of Gorontalo is dominated by the coralline floatstone facies. Characteristics of the coralline floatstone facies based on laboratory analysis showed an average specific gravity of 1.74 and an apparent specific gravity of 2.04. While the average percentage of limestone water absorption is 8.41%.